Advances in Biological Tissue Biomechanics - Lee, Chung-Hao; Liao, Jun (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Advanced experimental and computational biomechanics have become essential components to better understand the physiological and pathological conditions of biological tissues in the human body. Recent advances in medical imaging modalities, image segmentation, tissue characterization experiments, and predictive computer simulations have made major contributions to transforming current therapeutic paradigms, towards the facilitation of patient-specific diagnostics and individualized surgery planning. This Special Issue of Bioengineering on Advances in Biological Tissue Biomechanics, therefore, focuses on research dealing with cutting-edge experimental and computational methodologies for biomechanical investigations of tissues in the human body system across multiple spatial and temporal scales.